Glutaric Acidemia Type-1: A Metabolic Challenge - Munir, Muhammad Usman; Batool, Monaza; Khan, Muhammad Qaiser Alam; Ahmed, Nisar (Pakistan Armed Forces Medical Journal, 2025)
Glutaric Acidemia Type-1 (GA-1) is characterized by glutaryl-CoA dehydrogenase (GCDH) impairment. This enzyme deficit causes harmful metabolites, particularly glutaric acid, to accumulate in affected persons' tissues and fluids. We report a case series of four patients in our study with complaints of macrocephaly, poor head holding, and gross developmental delay. On the biochemical analysis, they had elevated levels of GA in urine organic acid level which confirmed the presence of GA type-1.